Rethinking modern theories of ageing and their classification: the proximate mechanisms and the ultimate explanations - Chmielewski, Piotr (Anthropological Review, 2017)
For a very long time, ageing has been an insurmountable problem in biology. The collection of age-dependent changes that render ageing individuals progressively more likely to die seemed to be an intractable labyrinth of alterations and associations whose direct mechanisms and ultimate explanations were too complex and difficult to understand. The science of ageing has always been fraught with insuperable problems and obstacles. In 1990, Zhores Medvedev presented a list of roughly 300 different hypotheses to illustrate this remarkable complexity of the ageing process and various approaches to understanding its mechanisms, though none of these hypotheses or aspect theories could be the general theory of senescence. Moreover, in the light of current data some of these ideas are obsolete and inapplicable. Nonetheless, the misconception that there are hundreds of valid theories of ageing persists among many researchers and authors. In addition, some of these obsolete and discarded hypotheses, such as the rate of living theory, the wear and tear theory, the poisoning theory, or the entropy theory still can be found in today’s medical textbooks, scientific publications aimed at the general public, and even in scientific writing. In fact, there are only several modern theories of ageing supported by compelling evidence that attempt to explain most of the data in current gerontology. These theories are competing to be a general and integrated model of ageing, making it unlikely that all of them could be true. This review summarises briefly several selected modern theories of senescence in the light of the contemporary knowledge of the biological basis for ageing and current data.